Where the past begins [compact disc, unabridged] : a writer's memoir - Tan, Amy (Harper Audio, 2017)
From New York Times bestselling author Amy Tan, a memoir on her life as a writer, her childhood, and the symbiotic relationship between fiction and emotional memory.